A SYSTEMATIC REVIEW OF THE EFFECTS OF TALENT, DIGITAL TRAINING, AND CAREER DEVELOPMENT ON PERFORMANCE THROUGH JOB COMPETENCY - Umar Hamdani; Budi Eko Soetjipto; Ludi Wisnu Wardhana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This article aims to systematically examine the relationship between talent development, digital skills training, and career advancement opportunities on employee performance, with job competency serving as an intervening variable. The approach employed is a Systematic Literature Review (SLR) based on the PRISMA protocol, analyzing 67 Scopus-indexed scientific articles published within the last five years. The synthesis results reveal that all three core variables consistently contribute positively to performance improvement, both directly and indirectly through job competency. The findings also highlight that most existing studies remain fragmented and have not yet fully integrated a comprehensive multi-path mediation model. Furthermore, there is a prevailing tendency toward descriptive approaches and a lack of cross-cultural and cross-sectoral empirical testing. This study proposes a new conceptual model based on the integration of strategic HRM variables and offers a theoretical contribution to the development of competency-based performance frameworks. The practical implications are directed toward organizations in designing adaptive, digital-based, and sustainability-oriented human resource development strategies.